2023
DOI: 10.1002/gj.4731
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements of sulfides in the Dengjiashan Pb–Zn deposit from West Qinling, China: Implications for mineralization conditions and genesis

Abstract: Dengjiashan is a large‐scale Pb–Zn deposit discovered in the western part of the Xicheng ore field within the West Qinling metallogenic belt. Information regarding the distribution and occurrence of trace elements in ore minerals and mineralization, as well as the genesis of this deposit, remains scarce. Laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) analysis and elemental mapping were used to determine the distribution and occurrence of trace elements in the sulfide minerals of the De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(154 reference statements)
0
0
0
Order By: Relevance
“…Numerous studies have investigated the substitution mechanisms of trace elements in the sphalerite lattice, suggesting that divalent cations such as Mn 2+ , Fe 2+ , Cd 2+ , Co 2+ , and Ni 2+ could directly replace Zn 2+ in the crystal lattice of sphalerite because their ionic radii and valence states are similar to Zn 2+ [34][35][36]38,39]. Monovalent (Ag + , Cu + ), trivalent (Sb 3+ , Sn 3+ ), and tetravalent (Sn 4+ ) cations with larger ionic radii and different valence states are usually substituted for Zn 2+ in the sphalerite lattice by forming cation groups, such as (Ag, Cu) + + (Sb, Sn) 3+ ↔ 2Zn 2+ and 2(Ag, Cu) + + Sn 4+ ↔ 3Zn 2+ [34,[40][41][42][43][44][45][46][47]. However, in sphalerite from the Caoziwa deposit, the concentration of Pb varies in several orders of magnitude, implying that it is significantly affected by Pb-rich inclusions (e.g., galena).…”
Section: Trace Element Speciation In Sulfidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the substitution mechanisms of trace elements in the sphalerite lattice, suggesting that divalent cations such as Mn 2+ , Fe 2+ , Cd 2+ , Co 2+ , and Ni 2+ could directly replace Zn 2+ in the crystal lattice of sphalerite because their ionic radii and valence states are similar to Zn 2+ [34][35][36]38,39]. Monovalent (Ag + , Cu + ), trivalent (Sb 3+ , Sn 3+ ), and tetravalent (Sn 4+ ) cations with larger ionic radii and different valence states are usually substituted for Zn 2+ in the sphalerite lattice by forming cation groups, such as (Ag, Cu) + + (Sb, Sn) 3+ ↔ 2Zn 2+ and 2(Ag, Cu) + + Sn 4+ ↔ 3Zn 2+ [34,[40][41][42][43][44][45][46][47]. However, in sphalerite from the Caoziwa deposit, the concentration of Pb varies in several orders of magnitude, implying that it is significantly affected by Pb-rich inclusions (e.g., galena).…”
Section: Trace Element Speciation In Sulfidesmentioning
confidence: 99%
“…George et al (2015) proposed that there is an isomorphic substitution of Bi 3+ + (Ag, Tl) + ↔ 2Pb 2+ in galena [39]. Meanwhile, Guo et al (2023) suggested that Ag, Sn, Cd, Tl, and Bi could enter the galena by the isomorphic substitution of Bi 3+ + (Cd, Sn) 2+ + (Ag, Tl) + ↔ 3Pb 2+ [47]. In the Caoziwa deposit, the time-resolved analytical signals of galena are relatively flat (Figure 6d), indicating that the detected elements mainly enter the galena grains by isomorphic substitution.…”
Section: Sources Of Ore-forming Materialsmentioning
confidence: 99%